PSIII-2 Effects of temperament on adaptation to prolonged water restriction. (5th December 2019) - Bruno, Kelsey; Ahlberg-Smith, Cashley; Meador, Heather; Calvo-Lorenzo, Michelle S; DeSilva, Udaya; Krehbiel, Clint; Mateescu, Raluca G; Place, Sara E; Rolf, Megan; Vanoverbeke, Deb; Wilson, Blake K; Richards, Chris
Abstract: It is generally accepted that "temperamental" cattle are more anxious or experience higher stress, causing differences in intake and performance. The objective of this study was to examine whether temperament affects how steers perform during prolonged water restriction, a chronic stressor. Steers from numerous sources in 4 groups (n = 469) were randomly allocated to 2 weight blocks. Steers were fed ad libitum 3 times a day for 70 d. After a 28 d step-down period, steers were maintained at 50% of normal water allotment for 42 d while feed continued to be offered ad libitum. Individual feed and water intake (WI) were measured daily using an Insentec RIC feeding system. Body weight, exit velocity (EV; measured over 1.5m), and chute score (CS; reported on a 1–4 scale) were measured every 14 d. Lower scores indicate calmer temperament. Due to the study design, DMI, ADG, G:F, and WI were split into 7 periods (d 0–28, 28–70, 0–70, 98–140, 98–112, 112–126, and 126–140). Data were analyzed using the MIXED procedure of SAS where the model included EV, CS, the interaction, and block; group was included as a random effect. Gain, DMI, and G:F d 0–28 were affected by both CS and EV. Slow EV steers had higher DMI than fast EV steers (P < 0.02) during d 28–70 and 0–70. During d 28–70, intermediate CS steers had the highest DMI (P < 0.05). During d 0–70 and 98–140, intermediate CS steers had the highest ADG (P < 0.05). All measures of DMI and WI were higher in the heavy weight block (P < 0.05); ADG and G:F were also higher in the heavy weight block during d 0–70 (P < 0.001). This experiment indicates that there may be performance benefits for steers with intermediate CS during long periods of water restriction.